Francine-Brunel-Reeves : portrait d’une chercheuse atypique ou quand la pratique appelle la recherche... - Bolduc, Marc (Rabaska : revue d'ethnologie de l'Amérique française, 2008)
This article offers a portrait of Francine Brunel-Reeves, an independent researcher who has followed an exceptional course throughout her active life. It begins with a short biography of this artist, perfomer, educator and independant researcher who has split her life between France, Québec and the United States of America. The second section describes the current state of her work and the theoretical approaches that have delineated her research not only in the field of ethnology, but also in anthropology, musicology and mythology.
Publisher: Société québécoise d’ethnologie